Taxonomic partitioning of Cyrtodactylus louisiadensis (Lacertilia: Gekkonidae) from Papua New Guinea - Kraus, Fred (Zootaxa, 2008)
As recently understood, the gecko species Cyrtodactylus louisiadensis (de Vis, 1892) ranges across eastern New Guinea and adjacent islands, the Solomon Islands, and northern Queensland. Within that portion of its range encompassed by Papua New Guinea I show that five species are currently masquerading under this appellation. Two of these occur in sympatry at the type locality for the species, Sudest Island. Because the type specimen is lost, the taxonomy of this complex has been confused, and two species are present at the type locality, I designate a neotype for C. louisiadensis so as to stabilize taxonomy within this complex. I describe the four additional species, C. epiroticus sp. nov., C. klugei sp. nov., C. robustus sp. nov., and C. tripartitus sp. nov., which differ from each other in a variety of scalational, mensural, and color-pattern features. Four of these species are confined to single islands off the southeastern peninsula of New Guinea. The fifth occupies the eastern rim of New Guinea.